Serotipificación de Escherichia coli aislados a partir de superficies vivas e inertes en un mercado de carne de pollo (Lima, Perú) - Morales-Cauti, Siever (2020)
The aim of this study was to identify and serotype isolate strains from vendors’ hands, chopping boards and vending tables of 50 chicken meat stalls in a market in San Juan de Miraflores district, Lima, Peru. The sampling was carried out with sterile swabs on the indicated surfaces. The Stuard medium was used to transport the samples to the laboratory. The enrichment was carried out in trypticase soy broth and the isolation was developed on McConkey agar. Positive lactose colonies compatible with E. coli were identified by standard biochemical tests. Serotyping was performed using the method described by Kauffman to detect somatic (O) and flagellar (H) antigens with specific SERUNAM antisera. Results showed that 42% (63/150) of the samples were identified as E. coli, and 58 viable strains were serotyped, belonging to 40 serotypes, where O6H10 was the most frequent (10.3%, 6/58).